AN ASSESSMENT OF HOUSEHOLD ENERGY CONSUMPTION IN BIDA AND ITS ENVIRONS, NIGER STATE, NIGERIA - Dangana.K; Liman H.M; Sallau, Osesienemo Racheal (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The study examined the relationship between household size and energy consumption in Bida and its environs. Based on the population of the study area, the total sample size was 398 with 80 households each from three wards and 79 household each from two wards. The structured questionnaires were administered to the 398 households, however only 388 questionnaires were retrieved back, the rest were misplaced or the respondents were absents as at the time of retrieval. The data was analyzed using descriptive statistic and chi-square was use to test the relationships. The result shows that fuel wood and charcoal are the main types of energy for cooking, while for room lighting electricity dominates kerosene, household size correlate positively with energy consumption. It is therefore, recommended that since the use of fuel wood and charcoal dominates and this may lead to serious deforestation, alternatives such as gas, solar and wind energy should be made available at affordable prices and peoples should be encouraged to use them.